Advancing implementation science in community settings: the implementation strategies applied in communities (ISAC) compilation - Laura E. Balis; Bailey Houghtaling; Whitney Clausen; Hannah Lane; Marilyn E. Wende; Emiliane Pereira; Gabriella M. McLoughlin; Samantha M. Harden (International Journal of Behavioral Nutrition and Physical Activity)
Abstract Background Implementation strategies have predominantly been operationalized and studied in clinical settings. Implementation strategies are also needed to improve evidence-based intervention (EBI) integration in community settings, but there is a lack of systematic characterization of their use, which limits generalizability of findings. The goals of this study were to determine which implementation strategies are most used to deliver primary prevention EBIs in community settings, develop a compilation and pragmatic strategy selection process with accompanying guidance tools, and understand practitioners’ preferences for dissemination. Methods Purposive and snowball sampling was used to recruit community setting researchers and practitioners delivering primary prevention EBIs (nutrition, physical activity, tobacco prevention) in community settings: education, social services, city planning and transportation, workplaces, recreation/sport, faith-based, and other public health organizations. Semi-structured interviews were conducted using a guide based on the reach, effectiveness, adoption, implementation, maintenance (RE-AIM) framework. Participants were asked to describe barriers experienced and strategies used to overcome them within each RE-AIM dimension. Practitioners were also asked about preferred dissemination strategies, prompted by Diffusion of Innovations theory concepts of sources (who provides information) and channels (how information is provided). A rapid deductive approach was used to analyze findings with a coding matrix aligned with the interview guide. Results Researchers (n = 10) and practitioners (n = 8) across all targeted settings and intervention outcomes completed interviews. Interviewees shared unique implementation strategies (N = 40) which were used to overcome barriers related to multiple RE-AIM dimensions, most commonly implementation (n = 29) and adoption (n = 27). Most frequently mentioned implementation strategies were conduct pragmatic evaluation (n = 31), provide training (n = 26), change adaptable program components (n = 26), and leverage funding sources (n = 21). Webinars (n = 6) and listservs/newsletters (n = 5) were the most mentioned dissemination channels; national public health organizations (n = 13) were the most mentioned sources. Conclusions Results reflect commonly used implementation strategies in community settings (e.g., training, technical assistance) and add novel strategies not reflected in current taxonomies. Dissemination preferences suggest the need to involve broad-reaching public health organizations. The resultant compilation (Implementation Strategies Applied in Communities) and strategy selection process provide resources to assist researchers and practitioners in applying strategies and improving EBI delivery in community settings.